Perlakuan Akuntansi Aset Biologis Tanaman Tebu Pada PTPN XI PG. Poerwodadie Magetan - Sasmito Widi Nugroho; Merlin Nilam Lapenia; Shinta Noor Anggraeny (JAMER : Jurnal Akuntansi Merdeka, 2020)
Abstract— This research aims to determine the accounting treatment of biological assets in terms of recognition, measurement and presentation in financial statements and also aims to determine the comparison of the accounting treatment of biological assets of companies based on Financial Accounting Standards namely PSAK 69 Agriculture. This study uses qualitative research methods with a case study approach conducted at PTPN XI PG. Poerwodadie. Data collected by interview, documentation and literature study. PSAK 69 regulates the accounting treatment for the agricultural sector which includes the recognition, measurement and disclosure of agricultural activities. The results showed that PTPN XI PG. Poerwodadie which is engaged in plantations recognizes biological assets in the form of estate crops classified into immature and mature plants. Biological assets are measured at cost and are presented on the balance sheet in the heading of Non-current Assets. PT. Perkebunan Nusantara XI PG. Poerwodadie still has not applied PSAK 69 Agriculture, it can be seen in the company's financial statements that measure its biological assets at fair value rather than acquisition costs. Keywords—: Biological Asset Accounting; Financial Statements; PSAK 69.